Analisis Fraud Diamond Theory terhadap Kecurangan Akuntansi di Sektor Pemerintahan - Yulia Deby Pratiwi; Muhammad Aufa (Universitas 45 Surabaya, 2024)
This study aims to prove the effect of compensation suitability, internal control system, organizational culture, and competence on the occurrence of fraud in the government sector. The sample used in this study was 52 employees in 3 Gresik Regency government offices using purposive sampling. This study uses multiple linear regression analysis techniques. The regression results show that the internal control system has an effect on the tendency of fraud, while compensation suitability, organizational culture and competence have no effect on the tendency of fraud in the Gresik Regency government.